2014
DOI: 10.1016/j.iccn.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Waiting for a heart or lung transplant: Relatives’ experience of information and support

Abstract: Waiting for a heart or lung transplant: Relatives' experience of information and support.Ivarsson, Bodil; Ekmehag, Björn; Sjöberg, Trygve Link to publication Citation for published version (APA): Ivarsson, B., Ekmehag, B., & Sjöberg, T. (2014). Waiting for a heart or lung transplant: Relatives' experience of information and support. Intensive & Critical Care Nursing, 30(4), 188-195. DOI: 10.1016/j.iccn.2014 General rights Copyright and moral rights for the publications made accessible in the public portal are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Perhaps there is a need to redefine the meaning of recovery after a HTX, because recovery generally implies a return to 'normal'. 26 We know from previous research 27,28 that being a relative of a HTR is very stressful. Even though it was not the aim of this study, the informants described their concern for their relatives in terms of a lack of information and a need for support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps there is a need to redefine the meaning of recovery after a HTX, because recovery generally implies a return to 'normal'. 26 We know from previous research 27,28 that being a relative of a HTR is very stressful. Even though it was not the aim of this study, the informants described their concern for their relatives in terms of a lack of information and a need for support.…”
Section: Discussionmentioning
confidence: 99%
“…We know from previous research 27,28 that being a relative of a HTR is very stressful. Even though it was not the aim of this study, the informants described their concern for their relatives in terms of a lack of information and a need for support.…”
Section: Discussionmentioning
confidence: 99%
“…Research also reveals that religious beliefs and cultural values can influence transplant recipients’ experiences with organ transplantation and their expectations of its outcomes (Ivarsson et al., 2014). Among Muslims, faith, religion and spirituality are not viewed in isolation, but rather they are part of the lived experience of being Muslim (Salman and Zoucha, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There was no current research found implementing or evaluating supportive interventions for support persons despite the fact that a number of authors discussed the need for healthcare professionals to attend to family caregivers' experiences (Kurz, 2002;Rodrigue & Baz, 2007) and provide added informational and psychological support to them (Meltzer & Rodrigue, 2001;Stubblefield & Murray, 2002). There was only one recent qualitative descriptive study exploring relatives' perceptions of information and support received during the waiting period (Ivarsson et al, 2014). Ivarsson et al found that family members reported dissatisfaction with the amount and timing of information received from the healthcare team, and indicated a need for more assistance with the patient's daily activities.…”
Section: Need For Supportmentioning
confidence: 99%